Development of Green Building Evaluation for Capacity Building of Civil Engineering Students to Realize Sustainable Development - Rina Marina Masri; Iskandar Muda Purwaamijaya; Irma Widianingsih; Btari Mariska Purwaamijaya (Faculty of Teacher Training and Education Universitas Sebelas Maret Surakarta, 2023)
The purpose of writing this article is to determine the level of Civil Engineering capacity in the development of green buildings to realize sustainable development. Civil engineering really considers advances in transportation technology, environmental changes such as climate, soil structure and natural disasters as well as the development of green buildings to realize sustainable development. Civil engineering is used to design and oversee the construction of infrastructure. However, the facts on the ground show that there are still many who think that the construction of green buildings is not the responsibility of civil engineering personnel but the responsibility of spatial planning personnel. Constraints from the unaccommodated green building by civil engineering personnel of UPI Bandung gave rise to the author's idea to conduct an evaluation of green building development to increase the capacity of Civil Engineering in realizing sustainable development. The activity method is descriptive activity through online and offline face-to-face activities, discussions, practicum, pre-test and post-test. The population is civil engineering students of FPTK UPI Bandung who are still active as students. The sampling technique was done randomly. The tools used are computer hardware and software, tests, questionnaires and observation sheets. Data The primary data taken is data from activity participants and secondary data in the form of satellite images of housing locations. The data analysis technique used is understanding analysis, participants' attitudes and skills as well as spatial analysis. Based on the results and discussion of the research, some research findings that can be concluded regarding the level of understanding of respondents in analyzing green building development to realize sustainable development are that the implementation of appropriate standard operating procedures to explain the analysis of green building evaluation development to realize sustainable development can increase the capacity of Civil Engineering.